Rapid Progression of Coronary Atherosclerosis: A Review. (28th December 2015) - Shah, Priyank; Bajaj, Sharad; Virk, Hartaj; Bikkina, Mahesh; Shamoon, Fayez
Abstract : Atherosclerosis is chronic disease, the prevalence of which has increased steadily as the population ages. Vascular injury is believed to be critical initiating event in pathogenesis of spontaneous atherosclerosis. Syndrome of accelerated atherosclerosis has been classically described in patients undergoing heart transplantation, coronary artery bypass graft, and percutaneous transluminal coronary angioplasty. In contrast to spontaneous atherosclerosis, denuding endothelial injury followed by thrombus formation and initial predominant smooth muscle cell proliferation is believed to be playing a significant role in accelerated atherosclerosis. There is no universal definition of rapid progression of atherosclerosis. However most studies describing the phenomenon have used the following definition: (i) > or = 10% diameter reduction of at least one preexisting stenosis > or = 50%, (ii) > or = 30% diameter reduction of a preexisting stenosis <50%, and (iii) progression of a lesion to total occlusion within few months. Recent studies have described the role of coronary vasospasm, human immunodeficiency virus, various inflammatory markers, and some genetic mutations as predictors of rapid progression of atherosclerosis. As research in the field of vascular biology continues, more factors are likely to be implicated in the pathogenesis of rapid progression of atherosclerosis.